Public Sector Reform: What Works and Why? An IEG evaluation of World Bank Support - Independent Evaluation Group (Washington, DC : World Bank, 2012)
The World Bank support for public sector reform has grown notably in recent years. To address the questions of what is working and why in this area, the Independent Evaluation Group (IEG) has examined Bank lending and other support for public sector reform in four areas: public financial management, administrative and civil service, revenue administration, and anticorruption and transparency. A majority of countries that borrowed to support public sector reform improved their performance in some dimensions, but there were shortcomings in important aspects. Middle-income borrowers saw improvements in their public sector quality more frequently than low-income borrowers, even though the low-income group usually had greater needs for public sector improvement. Performance usually improved for public financial management, tax administration, and transparency, but not for civil service. Direct measures to reduce corruption, such as anticorruption laws and commissions, rarely succeeded, as they often lacked the necessary support from political elites and the judicial system.